2011
DOI: 10.1002/ijch.201100141
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film Growth on Quasicrystalline Surfaces

Abstract: The surfaces of quasicrystals have proved to be a very interesting playground for thin film growth. They offer a complex potential energy surface where heterogeneous nucleation of islands at specific quasilattice sites is frequently observed. These islands tend to locally adopt the symmetry of the quasicrystalline substrate. For some specific adsorbates, a complete 2‐dimensional quasiperiodic metal overlayer is even formed. Other interesting phenomena are also observed in the multilayer regime. This includes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The clean surfaces of QCs have been used as aperiodic templates to prepare thin lms with novel structures. 63,78 It is predicted that the quasicrystalline order of the substrate can be propagated into the overlayer when a subset of quasilattice sites acts as preferential adsorption sites for deposited atoms or molecules. This is one way to construct quasicrystalline structures of single elements or molecules, which will be useful for studying the properties intrinsic to quasicrystalline structures by excluding the inuence of chemical complexity.…”
Section: Overlayer Growth On the Quasicrystalline Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The clean surfaces of QCs have been used as aperiodic templates to prepare thin lms with novel structures. 63,78 It is predicted that the quasicrystalline order of the substrate can be propagated into the overlayer when a subset of quasilattice sites acts as preferential adsorption sites for deposited atoms or molecules. This is one way to construct quasicrystalline structures of single elements or molecules, which will be useful for studying the properties intrinsic to quasicrystalline structures by excluding the inuence of chemical complexity.…”
Section: Overlayer Growth On the Quasicrystalline Surfacementioning
confidence: 99%
“…In fact, a large variety of elements and molecules have been deposited on the QC surfaces and the resulting ordering in the epitaxial layers has been studied. 63,78 In most cases, the overlayer thus obtained forms a monolayer of pseudomorphic lm, i.e., a lm forced to mimic the structure of the quasicrystalline substrate. Sharma et al recently reported the rst 3D quasicrystalline lms (multilayer Pb lms) grown on the surface of i-Ag-In-Yb.…”
Section: Overlayer Growth On the Quasicrystalline Surfacementioning
confidence: 99%
“…Therefore, we can see the limits of the present thermodynamic approach to the present nucleation mechanisms. In this respect, the deposition of metallic atoms onto QC clean surfaces under ultrahigh vacuum by Fournée et al 34 clearly shows how complex the nucleation mechanisms can be. In order to further elucidate this iQC-mediated nucleation mechanism during solidification, ab initio/MD calculations and maybe in situ diffraction experiments should be performed.…”
Section: Resultsmentioning
confidence: 99%
“…For the determination of the electronic and crystallographic structures of Al-based CMA surfaces, millimeter-sized single crystals have commonly been used when available. These works have highlighted complex energy landscapes, characteristics exploited to propagate complexity in elemental and molecular thin films [10,11,12]. For specific systems and under particular growth conditions, CMA have also been formed voluntarily or fortuitously as surface alloys [13].…”
Section: Introductionmentioning
confidence: 99%